2016
DOI: 10.1177/1524839916628865
|View full text |Cite
|
Sign up to set email alerts
|

Providers’ Views on a Community-Wide Patient Navigation Program

Abstract: The DuPage Patient Navigation Collaborative (DPNC) adapted and scaled the Patient Navigation Research Program’s intervention model to navigate uninsured suburban DuPage County women with an abnormal breast or cervical cancer screening result. Recent findings reveal the effectiveness of the DPNC in addressing patient risk factors for delayed follow-up, but gaps remain as patient measures may not adequately capture navigator impact. Using semistructured interviews with 19 DPNC providers (representing the county … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…A qualitative study of providers’ views on a cancer care navigation program found it increased patient volume and facilitated use of existing community resources while reducing the burden on physicians, nurses, and case managers. 41…”
Section: Specific Roles For Navigators In Women’s Healthmentioning
confidence: 99%
“…A qualitative study of providers’ views on a cancer care navigation program found it increased patient volume and facilitated use of existing community resources while reducing the burden on physicians, nurses, and case managers. 41…”
Section: Specific Roles For Navigators In Women’s Healthmentioning
confidence: 99%
“…Our search for primary studies identified six [13][14][15][16][17][18] that described components of the Patient Navigation Research Program (PNRP) sufficiently to address Question 1. We highlight PNRPrelated studies because the PNRP represents the single largest study of patient navigation to date: 10 different patient navigation programs across the country focused on breast, cervical, colorectal, and prostate cancers from 2005 to 2010.…”
Section: Systematic Reviews and Primary Studiesmentioning
confidence: 99%
“…We highlight PNRPrelated studies because the PNRP represents the single largest study of patient navigation to date: 10 different patient navigation programs across the country focused on breast, cervical, colorectal, and prostate cancers from 2005 to 2010. 19 Three of our identified studies [13][14][15] focused on seven of the PNRP sites, two 16,17 focused on a scaled-up county-wide adaptation of the…”
Section: Systematic Reviews and Primary Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is recent increased interest in the role of health system navigators who support chronically ill older adults through health-care transitions (Coleman et al, 2006;de la Riva et al, 2016;Manderson et al, 2012;Pedersen & Hack, 2010). Health system navigators are nurses and other health-care professionals who collaborate across sites of care and endeavor to ensure safe and effective transitions through fostering coordination and continuity of care, early identification, and response to health changes and services such as care planning and education (Brown, 2012;Clark, Parker, Battaglia, & Freund, 2014;Coleman et al, 2006;Freund et al, 2008;Jamieson, Grealish, Brown, & Draper, 2014;Manderson et al, 2012;Monza, Harris, & Shaw, 2015).…”
Section: Background and Purposementioning
confidence: 99%